Pengaruh Kepemimpinan, Motivasi, Disiplin, dan Lingkungan Kerja Terhadap Kinerja Karyawan CV. Jauhan Engineering Indonesia - Ida Hariyanti; Roziana Ainul Hidayati (Jurnal Mahasiswa Manajemen, 2022)
Background - Employee performance is the ability of employees to carry out tasks, and performance is very necessary because with this performance it will be known how far the employee's ability to carry out the tasks assigned by the company. Employee performance will be very important for CV. Jauhan Engineering Indonesia, which is engaged in contracting, relies on the active role of all its Human Resources to improve employee performance. Objectives – This study aims to analyze the influence of leadership, discipline, motivation and work environment on the performance of employees at CV. Distance Engineering Indonesia. Design/Methodology/Approach – This research is a quantitative study with data collection techniques using primary data and informant data collection using questionnaires or questionnaire surveys. Findings - The results of this study indicate that the variables of leadership, motivation, and discipline have a positive and significant effect on the performance of CV employees. Distance Engineering Indonesia. While the Work Environment variable has a positive and insignificant effect on the performance of CV employees. Distance Engineering Indonesia. Research Implications – This research can be used as a reference for CV. Juhan Engineering Indonesia to improve employee performance by prioritizing leadership patterns and paying attention, making absolute decisions / decisions, motivating, communicating or directing employees, being firm, and giving punishments. Research Limitations - Research conducted by researchers has limitations, namely only focusing on permanent employees CV. Just stay away from Engineering Indonesia.